2004
DOI: 10.1086/379762
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen/Hydrogen Chemistry in the Inner Comae of Active Comets

Abstract: We have constructed a concentric-shell, one-dimensional kinetic model that examines the chemistry of hydrogen and oxygen species in detail. We have studied the effects of the reactions of the reactive OH, O(3 P), and O(1 D) species with themselves and with the abundant stable molecules in the inner coma of moderately and highly active comets. We find that the reactions (1) Oð 1 DÞ þ H 2 O ! 2OH and (2) Oð 3 PÞ þ OH ! O 2 þ H play important roles in the inner comae of active comets. Inclusion of reaction (2) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 52 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Any of the changes in the OH photochemistry proposed in Table 2 Dalgarno (1984) converted to solar photochemical rates by Huebner et al (1992) describes the measured points well, assuming an average Q(H 2 O) ¼ 3 ; 10 29 s À1 for this FOV. The points are not inconsistent with the dashed line, which is produced using the OH photochemical rates of Glinski et al (2004) and a lower Q(H 2 O) value. The photochemical rates of Morgenthaler et al (2001) result in the dotted line, which matches the outer points well, but begins to fall short of the inner point.…”
Section: Long-slit Observationsmentioning
confidence: 80%
See 4 more Smart Citations
“…Any of the changes in the OH photochemistry proposed in Table 2 Dalgarno (1984) converted to solar photochemical rates by Huebner et al (1992) describes the measured points well, assuming an average Q(H 2 O) ¼ 3 ; 10 29 s À1 for this FOV. The points are not inconsistent with the dashed line, which is produced using the OH photochemical rates of Glinski et al (2004) and a lower Q(H 2 O) value. The photochemical rates of Morgenthaler et al (2001) result in the dotted line, which matches the outer points well, but begins to fall short of the inner point.…”
Section: Long-slit Observationsmentioning
confidence: 80%
“…We use a numeric integrator to convert from particle number density as a function of cometocentric distance to column density as a function of projected cometocentric distance on the sky. This gives us the flexibility to easily include effects, such as quenching, that modify the basic Haser density profile, and experiment with the chemical reactions considered by Glinski et al (2004). We found that over the density ranges represented by our Hyakutake [O i] data, neither quenching nor chemical production of O 2 were significant.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations